Performance analysis of aircraft composite winglet. (2022) - Kolappan, S.; Neethi Manickam, I.; Robinston Jeyasingh Swikker, K.; Joe Patrick Gnanaraj, S.; Appadurai, M.
Abstract: In this work, the aerodynamic and structural investigation of the winglet is done experimentally. The lift force and the drag force are acted on the winglet. The modification is done in the winglet to improve the lift force capacity and minimize the drag effect. Several angles of attack such as 45 0, 55 0, 65 0 & clean wing is investigated in this work. The experimentation is done in the wind tunnel for several angles of attack on the winglet. Further, the experimentation value is compared with the theoretical value. The drag coefficient, maximum CI and minimum CD at various angle of attack is obtained from the experimentation. The prototype model is designed in CATIA V5 software. The ANSYS software is used for numerical analysis. From the numerical and experimental results, the effective winglet model is obtained.